PROBLEMATIKA DWIFUNGSI ABRI - Fatimah Aqilah Ichtiari; Ilma Nur Safira, Ismail Fauzan Ramadhan, Muhammad Adam Fahri A., Naswa Putri Nur Firdaus, Dadi Mulya (Jurnal Salome : Multidisipliner Keilmuan, 2024)
This research is intended to critically analyze the issue of the dual function of ABRI that occurred in Indonesia. The method that we use in this research is descriptive method with Bibliographic Writing Technique (Literature Review). Based on this technique, we found that the role of ABRI that dominant in the government cause a negative effect to civilians. The solution to this problem was remove the dual function of ABRI under Abdurrahman Wahid presidency, as one of the reform efforts in Indonesia.